Successful therapeutic approach in a patient with elephantiasic pretibial myxedema, - Marina Ferreira; Luciana Helena Zacaron; Annair Freitas do Valle; Aloisio Carlos Couri Gamonal (Sociedade Brasileira de Dermatologia, 2020)
Abstract Localized pretibial myxedema is a dermopathy whose treatment is a challenge in dermatology, occurring in 0.5-4% of patients with Graves' disease. This autoimmune thyroid condition stimulates the production of hyaluronic acid and glycosaminoglycans that are deposited particularly in the pretibial region. Clinically, it presents as a localized, circumscribed, and non-depressible infiltrate in plaques. Several treatment modalities have been proposed, and their results vary, with worse response observed in severe cases. This report presents the case of a patient with elephantiasic pretibial myxedema who was subjected to intralesional corticosteroid applications, resulting in an excellent and encouraging therapeutic response that was maintained.